La mobilité intermodale par les données billettiques. Analyses spatio-temporelles du réseau bus-métro de Rennes Métropole - Cyprien Richer (Unité Mixte de Recherche 8504 Géographie-cités, 2018)
This paper aims to analyse the intermodal practices of mobility in the bus-metro network of Rennes metropole. Intermodality being strongly linked to the use of urban public transport networks, the Rennes Métropole bus and metro network data provided by Keolis-Rennes provides a very significant part of daily intermodality. To compensate for the lack of information on destinations and correspondances in the ticketing data a reconstruction of trips was made on the basis of hypotheses provided by the literature. The research carried out in the "Mobilletic" project considerably deepened the understanding of the temporal and spatial dimensions of intermodal mobility within Rennes Métropole’s urban public transport network.